Evolution of Pore Characteristics for Bentonite Modified by an Ionic Soil Stabilizer during Hydration Processes - Wei Huang; Zili Feng; Huanran Fu; Wei Xiang (Adsorption Science & Technology)
An ionic soil stabilizer (ISS) is used to reinforce clay soils because the ISS can regulate the hydration processes and microstructures of clays. To evaluate the regulation of ISS, natural bentonite was modified by ISS at different concentrations in this research. Water vapour adsorption and X-ray diffraction (XRD) were carried out to interpret the hydration mechanism of bentonite. Meanwhile, an associated analysis between hydration pore structures and hydration mechanisms was implemented through variation of pore characteristic tests at different relative humidities (RHs) to distinguish multiscale pore adsorption of water during the corresponding hydration process. In addition, the pore characteristics were studied via XRD, nitrogen adsorption, and mercury injection tests. Finally, the origins that adsorbed water and pore structures changed by adding ISS were discussed. The results showed that for calcium bentonite, the cations hydrated first in the range of 0<RH<0.45~0.55, accompanied by the expansion of micropores. Then, adsorption occurred on the basal surface of the crystal layer in the range of 0.45~0.55<RH<0.8~0.9, with water mainly adsorbed into the mesopores. With further hydration when RH>0.8~0.9, diffused double layer (DDL) water ceaselessly entered the macropores. Both adsorbed water and multiscale pore size decreased when ISS was added to bentonite. The origins of the reduction were the regulation of ISS to exchangeable cations and the basal surface of the crystal layer.